EFEKTIFITAS PEMBERIAN TUNJANGAN PROFESI GURU (TPG) TERHADAP PROFESIONALISME GURU DI SEKOLAH DASAR NEGERI 171 PALEMBANG - Annisya Febriana; Syarwani Ahmad; Pahlawan Pahlawan (STKIP Pesisir Selatan, 2026)
Teachers’ pedagogical abilities in delivering instruction have not yet reached an optimal level, and professionalism remains a key element in improving educational quality. The Teacher Professional Allowance (TPG) functions as an essential support mechanism for fostering teachers’ ongoing professional growth. This study seeks to examine the effectiveness of the Teacher Professional Allowance in strengthening teacher professionalism at SD Negeri 171 Palembang, focusing on the stages of planning, implementation, evaluation, and follow-up. The research employed a descriptive qualitative method, incorporating observations, interviews, and document analysis. Data were analyzed through processes of reduction, organization, and conclusion drawing. The results demonstrate that the Teacher Professional Allowance contributes positively to teachers’ performance as professional educators. The allowance enhances teachers’ motivation to prepare well-developed learning materials and utilize engaging, interactive teaching approaches, which in turn contribute to improved learning achievements. Overall, the study concludes that teacher professionalism is closely influenced by their attitudes and conduct in fulfilling their responsibilities. The findings are consistent with Glickman’s theory, which posits that professional educators exhibit strong competencies and high motivation, enabling effective learning processes and the attainment of quality educational outcomes.